2007
DOI: 10.1111/j.1471-4159.2006.04353.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal NOS‐mediated nitration and inactivation of manganese superoxide dismutase in brain after experimental and human brain injury

Abstract: Manganese superoxide dismutase (MnSOD) provides the first line of defense against superoxide generated in mitochondria. SOD competes with nitric oxide for reaction with superoxide and prevents generation of peroxynitrite, a potent oxidant that can modify proteins to form 3-nitrotyrosine. Thus, sufficient amounts of catalytically competent MnSOD are required to prevent mitochondrial damage. Increased nitrotyrosine immunoreactivity has been reported after traumatic brain injury (TBI); however, the specific prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 93 publications
3
88
0
8
Order By: Relevance
“…Because GPx and CAT both control H 2 O 2 , they represent the major defense against ROS [14]. Decreased activity of Mn-SOD is a likely consequence of peroxynitrite after TBI, and could lead to further oxidative stress and progressively enhance peroxynitrite production as part of the secondary damage cascade [10]. Decreased activity of Cu/Zn-SOD in ipsilateral hippocampus of young animals post injury compromises defense capacities against oxidative stress [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because GPx and CAT both control H 2 O 2 , they represent the major defense against ROS [14]. Decreased activity of Mn-SOD is a likely consequence of peroxynitrite after TBI, and could lead to further oxidative stress and progressively enhance peroxynitrite production as part of the secondary damage cascade [10]. Decreased activity of Cu/Zn-SOD in ipsilateral hippocampus of young animals post injury compromises defense capacities against oxidative stress [39].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced production of reactive oxygen/nitrogen species (ROS/RNS) cause oxidative/ nitrosative stress [5,6] leading to damage in lipids, proteins and nucleic acids [7,8]. Oxidative stress-related cascades resulting from TBI have been implicated in cytoskeletal damage, mitochondrial dysfunction [9] and altered signal transduction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…SOD is a target of tyrosine nitration and nitration inactivates the enzyme. 34 Nitration and inactivation of SOD could lead to self-amplification of oxidative stress in the tissues progressively enhancing peroxynitrite production and secondary damage. It has been already demonstrated that CP-induced bladder damage involves peroxynitrite formation and protein nitration.…”
Section: Discussionmentioning
confidence: 99%
“…In other reactions involving oxidation of the Met 35 formation of methionine sulfoxide (MetO) occurs, which can be reduced back to methionine by MetO reductase. The activity of MetO reductase is reduced in AD brain (161).…”
Section: Application Of Redox Proteomics To Selected Neurodegenermentioning
confidence: 99%
“…The recovery rate of 3-NT-containing peptides was *55% as measured with UV-Vis detection. Recovery rate was increased by varying incubation time on the column and incorporating more washes (35). Immunopurification strategies have been recently employed for the characterization of 3-NT-modified proteins in CSF of human patients to better understand HIV-associated neurocognitive disorders (37).…”
Section: Fig 10 Outline Of Redox Proteomics Approachmentioning
confidence: 99%